Estimated evapotranspiration of rice based on pan evaporation as a surrogate to lysimeter measurement - Kamal, Md. Rowshon; Mohd Soom, Mohd Amin; Mojid, Mohammad Abdul; Yaji, M. (Springer, 2014)
Reference crop evapotranspiration (ET o), used to determine actual crop evapotranspiration, is often estimated from pan evaporation (EP) data. However, uncertainties in the relationship between ET o and EP often result in unreliable estimate of crop evapotranspiration. This study investigated the relationship between measured and estimated crop evapotranspirations, ET m and ET e, respectively, at tillering (9–30 days after transplanting, DAT) and mid-growth (51–72 DAT) stages of a rice variety. ET m was measured with a Marriott Tube-type Micro-lysimeter (hereafter referred to Micro-lysimeter) in a ponded rice field and ET e was estimated from EP, which was measured by employing the US Weather Bureau Class ‘A’ Evaporation Pan (hereafter referred to Class A Evaporation Pan). A strong linear relation (r 2 = 0.89) at the tillering stage and a weak relation (r 2 = 0.48) at the mid-growth stage were obtained between ET m and EP. The slope of this plot provided a pan-crop factor (K p K c), which was 0.81 at the tillering stage and 0.79 at the mid-growth stage. The ET e versus ET m relationship was also strongly linear (r 2 = 0.90) at the tillering stage but weakly linear (r 2 = 0.50) at the mid-growth stage. The pan-based method thus provided reliable estimates of evapotranspiration during the tillering stage of rice.